Vici и κῶμαι первых веков нашей эры на территории фракийских земель (По данным письменных источников) - Мартемьянов, А. П. (Давнина. Харківський історико-археологічний щорічник, 2016)
Summary A. Martemyanov. Vici and κῶμαι of the First Centuries AD in the Territory of Thracian Lands (According to the Data of Written Sources) In the article is making an attempt to determine how many villages in the territory of Lower Moesia and Thrace by written sources are fixed. The author gives the list of vici and κῶμαι of these provinces which are recorded by epigraphic data. There are 90 positions in this catalogue. In total, according to the author’s estimates, about 100 villages of the first centuries AD in the Thracian lands are known today owing to the data of written sources. Key words: villages, vici, κῶμαι, Lower Moesia, Thrace.